Logarithmic Laws

Logarithmic Laws

$$ \large \log_{a}{(xy)} = \log_{a}{x} + \log_{a}{y} $$
$\textit{Proof}$
Let $A=\log_{a}{x}$ and $B=\log_{a}{y}$.
Then $a^A = x$ and $a^B=y$.
\( \begin{align}
a^A \times a^B&= xy \\
a^{A+B} &= xy \\
A+B &= \log_{a}{(xy)} \\
\therefore \log_{a}{x}+\log_{a}{y} &= \log_{a}{(xy)}
\end{align} \)

$$ \large \log_{a}{\dfrac{x}{y}} = \log_{a}{x}-\log_{a}{y} $$
$\textit{Proof}$
Let $A=\log_{a}{x}$ and $B=\log_{a}{y}$.
Then $a^A = x$ and $a^B=y$.
\( \begin{align}
\dfrac{a^A}{a^B} &= \dfrac{a}{y} \\
a^{A-B} &= \dfrac{x}{y} \\
A-B &= \log_{a}{\dfrac{x}{y}} \\
\therefore \log_{a}{x}-\log_{a}{y} &= \log_{a}{\dfrac{x}{y}}
\end{align} \)

$$ \large \log_{a}{x^n} = n\log_{a}{x}$$
$\textit{Proof}$
\( \begin{align}
\log_{a}{x^n} &= \log_{a}{(\overbrace{x \times x \times \cdots \times x}^{n})} \\
&= \overbrace{\log_{a}{x} + \log_{a}{x} + \cdots + \log_{a}{x}}^{n} \\
&= n\log_{a}{x} \\
\therefore \log_{a}{x^n} &= n\log_{a}{x}
\end{align} \)

$$ \large \log_{a}{1} = 0$$
$\textit{Proof}$
\( \begin{align}
a^0 &= 1 \\
\therefore 0 &= \log_{a}{1}
\end{align} \)

$$\large \log_{a}{a} = 1$$
$\textit{Proof}$
\( \begin{align}
a^1 &= a \\
\therefore 1 &= \log_{a}{a}
\end{align} \)

Please ensure the following, as many students have often made the following mistakes.

$$ \large \begin{align}
\log_{a}{x} + \log_{a}{y} &\ne \log_{a}{(x+y)} \\
\log_{a}{x} – \log_{a}{y} &\ne \log_{a}{(x-y)} \\
\log_{a}{x} \times \log_{a}{y} &\ne \log_{a}{(xy)} \\
\dfrac{\log_{a}{x}}{\log_{a}{y}} &\ne \log_{a}{\dfrac{x}{y}}
\end{align}$$
It is important to remember that each rule works only if the base $a$ is the same for each term.

YouTube player

Example 1

Use the logarithmic laws to write $\log_{2}{3} + \log_{2}{7}$ as a single logarithm.

\( \begin{align} \displaystyle
\log_{2}{3} + \log_{2}{7} &= \log_{2}{(3 \times 7)} \\
&= \log_{2}{21}
\end{align} \)

Example 2

Use the logarithmic laws to write $\log_{4}{24}-\log_{4}{6}$ as an integer.

\( \begin{align} \displaystyle
\log_{4}{24}-\log_{4}{6} &= \log_{4}{\dfrac{24}{6}} \\
&= \log_{4}{4} \\
&= 1
\end{align} \)

Example 3

Use the logarithmic laws to write $2\log_{5}{4}-3\log_{5}{2}$ as a single logarithm.

\( \begin{align} \displaystyle
2\log_{5}{4}-3\log_{5}{2} &= \log_{5}{4^2}-\log_{5}{2^3} \\
&= \log_{5}{16}-\log_{5}{8} \\
&= \log_{5}{\dfrac{16}{8}} \\
&= \log_{5}{2}
\end{align} \)

Example 4

Use the logarithmic laws to write $\log_{a}{24}$ in terms of $x$ and $y$ given $x=\log_{a}{2}$ and $y=\log_{a}{3}$.

\( \begin{align} \displaystyle
\log_{a}{24} &= \log_{a}{(2 \times 2 \times 2 \times 3)} \\
&= \log_{a}{(2^3 \times 3)} \\
&= \log_{a}{2^3} + \log_{a}{3} \\
&= 3\log_{a}{2} + \log_{a}{3} \\
&= 3x + y
\end{align} \)

Example 5

Simplify $\dfrac{\log_{5}{729}}{\log_{5}{27}}$.

\( \begin{align} \displaystyle
\dfrac{\log_{5}{729}}{\log_{5}{27}} &= \dfrac{\log_{5}{3^6}}{\log_{5}{3^3}} \\
&= \dfrac{6\log_{5}{3}}{3\log_{5}{3}} \\
&= \dfrac{6}{3} \\
&= 2
\end{align} \)

 

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Ratio Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Related Articles

Responses

Your email address will not be published. Required fields are marked *